Cross-reactivity of rPvs48/45, a recombinant Plasmodium vivax protein, with plasma from Plasmodium falciparum endemic areas of Africa - Saidou Balam; Kazutoyo Miura; Imen Ayadi; Drissa Konaté; Nathan C. Incandela; Valentina Agnolon; Merepen A. Guindo; Seidina A. S. Diakité; Sope Olugbile; Issa Nebie; Sonia M. Herrera; Carole Long; et al. (PLoS ONE, 2025)
Background Ps48/45, a Plasmodium gametocyte surface protein, is a promising candidate for malaria transmission-blocking (TB) vaccine. Due to its relevance for a multispecies vaccine, we explored the cross-reactivity and TB activity of a recombinant P. vivax Ps48/45 protein (rPvs48/45) with plasma from P. falciparum-exposed African donors. Methods rPvs48/45 was produced in Chinese hamster ovary cell lines and tested by ELISA for cross-reactivity with plasma from Burkina Faso, Tanzania, Mali, and Nigeria. In addition, BALB/c mice were immunized with the rPvs48/45 protein formulated in Montanide ISA-51 and inoculated with a crude extract of P. falciparum NF-54 gametocytes to evaluate the parasite-boosting effect on rPvs48/45 antibody titers. Specific anti-rPvs48/45 IgG purified from African plasma was used to evaluate the ex vivo TB activity on P. falciparum, using standard mosquito membrane feeding assays (SMFA). Results rPvs48/45 protein showed cross-reactivity with plasma of individuals from all four African countries, in proportions ranging from 94% (Tanzania) to 40% (Nigeria). Also, the level of cross-reactive antibodies varied significantly between countries (p < 0.0001), with a higher antibody level in Mali and the lowest in Nigeria. In addition, antibody levels were higher in adults ( ≥ 17 years) than young children ( ≤ 5 years) in both Mali and Tanzania, with a higher proportion of responders in adults (90%) than in children (61%) (p < 0.0001) in Mali, where male (75%) and female (80%) displayed similar antibody responses. Furthermore, immunization of mice with P. falciparum gametocytes boosted anti-Pvs48/45 antibody responses, recognizing P. falciparum gametocytes in indirect immunofluorescence antibody test. Notably, rPvs48/45 affinity-purified African IgG exhibited a TB activity of 61% against P. falciparum in SMFA. Conclusion Plasma from African volunteers predominantly exposed to P. falciparum cross-recognized the rPvs48/45 protein. This, together with the functional activity of IgG, warrants further studies for the potential development of a P. vivax and P. falciparum cross-protective TB vaccine.